Assessment of nutrition knowledge and associated factors among secondary school students in Haramaya district, Oromia region, eastern Ethiopia: implications for health education - Edin, Alo; Jemal, Kedir; Ahmed, Ibsa Abdusemed; Gebremichael, Berhe; Bushra, Abdulmalik Abdela; Demena, Melake; Abdirkadir, Merian (Frontiers in Public Health, 2024)
Background: Nutrition knowledge stands as a cornerstone in facilitating informed dietary choices, thereby profoundly impacting overall health and lifestyle outcomes. Malnutrition often correlates with deficient nutritional knowledge, highlighting the critical need for comprehensive understanding in this domain. While Ethiopia has seen considerable research on nutritional status and associated factors, there remains a paucity of studies specifically addressing nutrition knowledge among secondary school students, particularly within the Haramaya District.Therefore, this study aimed to meticulously assess nutrition knowledge and its determinants among secondary school students in Eastern Ethiopia.: Employing an institutional-based cross-sectional design, we carefully selected 417 students from secondary schools in Haramaya District, Eastern Ethiopia, through simple random sampling. Data collection entailed structured interviews, with subsequent entry into Epi Data version 3.1 for meticulous analysis utilizing SPSS version 21 software. Descriptive statistics summarized participant characteristics, while both bivariable and multivariable logistic regression analyses were conducted to elucidate factors associated with nutritional knowledge, setting statistical significance at p-value < 0.05. Results: All 417 selected students participated in the study, yielding a commendable response rate of 100%. The median nutritional knowledge score among students stood at 58, with an interquartile range spanning from 44 to 66. Approximately 46.76% (95% CI: 42-51.59) of students exhibited good nutritional knowledge. Significant determinants of nutrition knowledge included sex (adjusted odds ratio [AOR] = 1.77, 95% CI: 1.03-3.04), being senior secondary students (AOR = 3.3, 95% CI: 1.95-5.73), and access to nutrition information (AOR = 3.3, 95% CI: 1.60-6.87). Conclusion: Our findings illuminate a notable level of nutritional knowledge among secondary school students in Haramaya District. However, discernible disparities in nutrition knowledge emerged based on gender, educational level, and access to nutrition information. These insights underscore the exigency of targeted interventions aimed at enhancing nutrition literacy among students, thereby fostering holistic health promotion endeavors.